HOW TO WRITE YOUR COMPUTER A POEM. - HO, JOSES (Michigan Quarterly Review)
The article focuses on the creative intersection between computational methods and poetic expression, exploring how code and algorithms can generate and critique language. Topics include using a Markov model to produce poetry from a social media corpus, employing programming to parody development-sector jargon, and reflecting on how machine-assisted writing blurs the line between satire and sincerity.